MCSE guide to managing a Microsoft Windows Server 2003 network, enhanced - Eckert, Jason W. (Course Technology Cengage Learning, 2006)
This full-color hands-on guide book has been enhanced to make learning even easier by offering more detailed lab setup instructions, expanded chapter summaries, and new practice exams that will reinforce the skills learned